Cognitive and Emotional Development of STEM Skills in Primary School Teacher Training through Practical Work - Guadalupe Martínez-Borreguero; Francisco Luis Naranjo-Correa; Milagros Mateos-Núñez (MDPI AG, 2022)
Several studies highlight that trainee primary school teachers show negative emotions towards learning and teaching STEM subjects with low levels of teacher self-efficacy in these areas. The general objective of this research was to analyse the cognitive, emotional and didactic development of STEM competences in trainee primary school teachers. Practical STEM experiences were designed and implemented to promote a positive evolution in the cognitive, affective and self-efficacy domains of future primary school teachers. A quasi-experimental research design was followed with a control group, experimental group, pre-test and post-test. The teaching methodology used was considered as the independent variable and the level of knowledge, the level of teaching self-efficacy and the emotions experienced when learning and teaching STEM content were considered as dependent variables. A non-probabilistic sample of 345 trainee primary school teachers took part in the study. The results led to the development of more than 70 STEM workshops. The inferential statistical analysis revealed the existence of statistically significant differences in all the variables of the study, detecting a positive evolution of the trainee teachers at a didactic, competence and emotional level. It is concluded that the use of practical STEM activities may lead to an improvement in the professional development of teachers and in the quality of science and technology teaching.